2014
DOI: 10.1021/cs500843a
|View full text |Cite
|
Sign up to set email alerts
|

Iridium, Rhodium, and Ruthenium Catalysts for the “Aldehyde–Water Shift” Reaction

Abstract: A series of half-sandwich complexes of iridium, rhodium, and ruthenium are shown to be active catalysts for the conversion of aldehydes and water to carboxylic acids. Depending on the catalyst, H2 is either released (the “aldehyde–water shift”) or transferred to a second equivalent of aldehyde (aldehyde disproportionation). Mechanistic studies suggest hydride transfer to be the selectivity-determining step along the reaction pathway. Using [(p-cymene)­Ru­(bpy)­OH2]­[OTf]2 as precatalyst, we demonstrate a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 22 publications
5
55
0
Order By: Relevance
“…The rst is dehydrogenation of ethanol to acetaldehyde, and the second is the reaction of acetaldehyde with water which named "aldehyde-water shi" (AWS) reaction to acetic acid. 17,18 As the reaction results of Fig. 3 shows, pure Cr 2 O 3 exhibits none of catalytic activity which indicates at least the rst step of dehydrogenation can only proceed on copper species.…”
Section: Results Of Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…The rst is dehydrogenation of ethanol to acetaldehyde, and the second is the reaction of acetaldehyde with water which named "aldehyde-water shi" (AWS) reaction to acetic acid. 17,18 As the reaction results of Fig. 3 shows, pure Cr 2 O 3 exhibits none of catalytic activity which indicates at least the rst step of dehydrogenation can only proceed on copper species.…”
Section: Results Of Characterizationmentioning
confidence: 96%
“…20,21 Recently, Heinekey et al reported that a series of (p-cymene) ruthenium(II) diamine complexes and p-arene (or cyclopentadienyl) complexes of iridium, rhodium, and ruthenium were shown to be active catalysts for the conversion of aldehydes and water to carboxylic acids. 17,18 However, all these homogeneous reaction systems have the obvious disadvantages on the separation of products and the recycling of catalyst. Thus a more attractive process for industrial application would be heterogeneous reaction system especially over the base metal catalysts, because of the convenience of catalyst separation, facile continuous process operation and cost effectiveness.…”
Section: -19mentioning
confidence: 99%
“…The strong interest in catalysis and electrocatalysis in aqueous medium has pushed ahead the study of metal hydrides in water. 54,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] The close thermodynamic links between redox potentials and hydrogen ion concentration should provide a particularly strong framework for understanding the chemistry of transition metal hydrides in buffered solutions. A wide range of acid-base indicators can be used in titrations.…”
Section: Water and Methanolmentioning
confidence: 99%
“…Similarly the complex [Ru(H 2 )(PPh 3 ) 2 (tpm)] 2+ , where tpm is tris(pyrazolyl)methane, has a pK a DCM 2.8. 182 Several bipyridine complexes have been studied (entries 11,14,15,33,81,136,157) with pK a LAC ranging from -4 to 26. The bipyridine ligand contributes 8 pK a units to a metal hydride complex according to the LAC system.…”
Section: Complexes With Nitrogen Donorsmentioning
confidence: 99%
“…Recent papers have focused on the production of hydrogen from the aqueous reforming of methanol which, whilst presenting its own unique challenges, results in very high atom efficiencies for hydrogen production. Ruthenium has shown itself to be the most widely investigated and flexible metal for alcohol dehydrogenation reactions although others, including for example; iron [87,89], cobalt [90], osmium [70,91] and iridium [92][93][94], have also been investigated with varying success.…”
Section: Resultsmentioning
confidence: 99%